2018
DOI: 10.1634/theoncologist.2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Primary Care Physicians in Childhood Cancer Survivorship Care: Multiperspective Interviews

Abstract: Childhood cancer survivors and their parents have low confidence in primary care physicians' ability to manage their survivorship care. Encouraging engagement in primary care is important to promote holistic follow-up care, continuity of care, and long-term surveillance. Survivors'/parents' confidence in physicians may be improved by better involving primary care physicians throughout treatment and early survivorship, and by introducing the concept of eventual transition to adult and primary services. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…In Australia, where patients can encounter geographical issues similar to our patients, Signorelli et al interviewed pediatricians and pediatric oncologists to better understand potential barriers to effective partnerships. Pediatricians reported that they were very willing to partner with pediatric oncologists or transplant physicians to care for patients, but expressed the need for more open communication to better support local care of pediatric oncology patients’ effects . Our own experience supports their findings.…”
Section: Discussionsupporting
confidence: 65%
“…In Australia, where patients can encounter geographical issues similar to our patients, Signorelli et al interviewed pediatricians and pediatric oncologists to better understand potential barriers to effective partnerships. Pediatricians reported that they were very willing to partner with pediatric oncologists or transplant physicians to care for patients, but expressed the need for more open communication to better support local care of pediatric oncology patients’ effects . Our own experience supports their findings.…”
Section: Discussionsupporting
confidence: 65%
“…19 Participants preferred hospital-based to community-based follow-up as their first choice, possibly reflecting early detachment from PCPs during treatment and lack of exposure to alternative models. 20,21 However, a purely hospital-based model is not sustainable as the number of survivors increases. 6,22 Risk-stratification may address the pitfalls of this model, and limited global resources, by triaging high-risk/complex survivors to multidisciplinary specialist-led care and lower risk survivors to shared or nurse/PCP-led care.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst PCPs seem willing to deliver childhood survivorship care, up to 58% of survivors in our study were unwilling to receive community-based follow-up, potentially reflecting survivors' emotional connection to their oncology team. 21,25,26 Additional PCP education, support, communication, 27 and a "culture change" to establish expectations from diagnosis may be required to ensure the success of community-based models. 26 Our data echoes existing literature showing that many survivors who are at high risk of developing late effects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing risk perceptions with increasing age is worrying because the risk of late effects actually increases as survivors age, 3 and only 23% of survivors in our population sought cancer-related care from their general practitioner. 4 More innovative interventions are required to re-engage survivors who are lost to follow-up to promote ongoing surveillance and the early detection of treatment-related sequelae. 5 Our data provide some understanding of the factors that may influence survivors' engagement, including survivors' future health concerns.…”
Section: Perceptions Of Future Health and Cancer Risk In Adult Survivmentioning
confidence: 99%